2010
DOI: 10.1007/jhep11(2010)007
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic symmetries of three-dimensional gravity coupled to higher-spin fields

Abstract: We discuss the emergence of W-algebras as asymptotic symmetries of higher-spin gauge theories coupled to three-dimensional Einstein gravity with a negative cosmological constant. We focus on models involving a finite number of bosonic higher-spin fields, and especially on the example provided by the coupling of a spin-3 field to gravity. It is described by a SL(3) \times SL(3) Chern-Simons theory and its asymptotic symmetry algebra is given by two copies of the classical W_3-algebra with central charge the one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
1,120
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(1,145 citation statements)
references
References 49 publications
(93 reference statements)
23
1,120
1
1
Order By: Relevance
“…In case of slN ⊕ slN Chern-Simons theory, the asymptotic symmetry is given by WN ⊕ WN [21]. Interestingly, WN does not contain slN as subalgebra -at least, not manifestly.…”
Section: Hs Algebras and Reductive Dual Pairsmentioning
confidence: 99%
“…In case of slN ⊕ slN Chern-Simons theory, the asymptotic symmetry is given by WN ⊕ WN [21]. Interestingly, WN does not contain slN as subalgebra -at least, not manifestly.…”
Section: Hs Algebras and Reductive Dual Pairsmentioning
confidence: 99%
“…the full higher spin conformal algebra [34][35][36]. The generators of G, which we label V s n , are identified with the wedge modes J (s) n , with |n| < s, and the level k is proportional to the CFT central charge c = 3 /2G.…”
Section: Jhep05(2014)052mentioning
confidence: 99%
“…The complexity of higher spin theories reduces drastically in three dimensions wherein it becomes possible to consistently truncate to a finite set of higher spin fields [17] and reformulate the theory with spin s ≤ N in terms of SL(N, R) × SL(N, R) Chern-Simons theory [18,19,20,21,22,23,24]. The works of [23,24] have shown that the asymptotic symmetry algebra of such higher spin theories on AdS 3 is (two copies of) the W N algebra.…”
Section: Introductionmentioning
confidence: 99%
“…The works of [23,24] have shown that the asymptotic symmetry algebra of such higher spin theories on AdS 3 is (two copies of) the W N algebra. This naturally generalizes the formulation of ordinary gravity on AdS 3 in terms of SL(2, R) × SL(2, R) Chern-Simons theory [25,26] and extends the associated asymptotic Virasoro symmetry [27] to the W N algebra.…”
Section: Introductionmentioning
confidence: 99%